Pengaruh Struktur Modal, Ukuran Perusahaan, Pertumbuhan Laba, dan Likuiditas terhadap Kualitas Laba - Lydia Mardiana; Endang Kartini; M. Wahyullah Wahyullah (Kompeten: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021. Samples were taken using purposive sampling. The criteria are based on the companies that issued financial statements during the study period. The data was obtained on the Indonesia Stock Exchange through the website www.idx.co.id. Data were analyzed using multiple linear regression. The results of this study indicate that the capital structure has a partial effect on earnings quality. On the other hand, firm size, profit growth, and liquidity have no partial effect on earnings quality. In addition, capital structure, firm size, profit growth, and liquidity simultaneously effect earnings quality. Keywords : Capital Structre, Firm Size, Profit Growth, Liquidity, Earnings Quality